ChemInform Abstract: Highly Diastereoselective Esterification of Ketenes Generated in situ from Acyl Chlorides with (R)‐Pantolactone Derivatives. Issue 18 (6th May 2014) - Yamagami, Takafumi; Hatsuda, Masanori; Utsugi, Masayuki; Kobayashi, Ryo; Moritani, Yasunori
Abstract: The use of NEt3 is found to be important to achieve high diastereoselectivity in this reaction.